2020
DOI: 10.7324/jabb.2020.80412
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of oligosaccharides and phenolic compounds by roasting pretreatment and enzymatic hydrolysis from spent coffee ground

Abstract: Spent coffee ground (SCG) is the waste generated during the preparation of instant coffee and is the source of industrially valuable organic compounds. In this article, SCG was pretreated by roasting at 150°C for 30 minutes and heated with water at 90°C for extracting carbohydrates and phenolic compounds, after which 1.0% (w/w) β-mannanase was applied for the hydrolysis of pretreated SCG. SCG is characterized in terms of its total sugar content by the anthrone-sulfuric assay and phenolic compounds by Folin−Cio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Their results, including the entire nutritional profile monitoring, reported carbohydrates as the main constituent of CS with 42% of value. Furthermore, the enzyme‐based hydrolyzation of SCG and CS carbohydrates into reducing sugars was proposed as a practical and green technique for sugars extraction into food‐applicable ingredients (Bhaturiwala & Modi, 2020). In addition, the transformation of insoluble fractions into soluble molecules, thereby reducing the particle size of samples, is another plus of enzyme hydrolysis as it can help in SCG and CS polysaccharide characterization (Cavanagh et al., 2023; Franca & Oliveira, 2022).…”
Section: Carbohydrates and Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results, including the entire nutritional profile monitoring, reported carbohydrates as the main constituent of CS with 42% of value. Furthermore, the enzyme‐based hydrolyzation of SCG and CS carbohydrates into reducing sugars was proposed as a practical and green technique for sugars extraction into food‐applicable ingredients (Bhaturiwala & Modi, 2020). In addition, the transformation of insoluble fractions into soluble molecules, thereby reducing the particle size of samples, is another plus of enzyme hydrolysis as it can help in SCG and CS polysaccharide characterization (Cavanagh et al., 2023; Franca & Oliveira, 2022).…”
Section: Carbohydrates and Fibersmentioning
confidence: 99%
“…Results showed that the mainly present sugars were mannose, mannobiose, mannotriose, and mannopentose, and that the obtained extract had prebiotic properties. An oligosaccharides extraction from SCG procedure was proposed by Bhaturiwala and Modi (2020) involving a series of sequential treatments. The best yield of polysaccharides (33.25%) was obtained using the central composite design, applying a roasting step at 160°C for 10 min with a liquid/solid ratio of 15 mL/g and a β‐mannanase enzymatic hydrolysis of the treated materials.…”
Section: Carbohydrates and Fibersmentioning
confidence: 99%
“…The mannanase of each fungus and incubation condition was specifically different for the reducing sugar result of SCG, for instance, Streptomyces sp. (Bhaturiwala and Modi, 2020) was used 353.4 U/mL of mannanase to degrade SCG for 20 hours at 45 °C with 60 rpm gained 0.089 g/g SCG and A. niger mannanase (Favaro et al, 2020) unspecified unit enzyme can produce reducing sugar ~0.009 g/g SCG under 50 °C for 24 hours with 30 rpm. A. pullulans NRRL 58524 crude mannanase (66.7 U/mL) was more attractive because it produced reducing sugar 0.61 g/g SCG at hot temperatures (55 °C) for 5 days 9 h. Besides, the substrate condition was affected to get optimum enzymatic hydrolysis, for example, the pretreatment of SCG by hot temperature.…”
Section: Scg Mannan Hydrolysismentioning
confidence: 99%